Effectiveness of medication self-management, self-monitoring and a lifestyle intervention on hypertension in poorly controlled patients: The MEDICHY randomized trial - Unda Villafuerte, Fabián; Llobera Cànaves, Joan; Estela Mantolan, Andreu; Bassante Flores, Patricia; Rigo Carratalà, Fernando; Requena Hernández, Ana; Oliver Oliver, Bartolomé; Pou Bordoy, Joan; Moreno Sancho, María Lucía; Leiva, Alfonso; Lorente Montalvo, Patricia, The MEDICHY Group; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Uncontrolled hypertension is a common problem worldwide, despite the availability of many effective antihypertensive drugs and lifestyle interventions. We assessed the efficacy of a multi-component intervention in individuals with uncontrolled hypertension in a primary care setting. Methods This study was a randomized, multicenter, parallel, two-arm, single-blind controlled trial performed in primary healthcare centers in Mallorca (Spain). All participants were 35 to 75-years-old and had poorly controlled hypertension. Patients were randomly assigned in a 1:1 ratio to a control group (usual care) or an intervention group (self-monitoring of blood pressure, self-titration of hypertensive medications, dietary interventions, and physical activity interventions). The primary outcome was decrease in the mean SBP at 6 months relative to baseline. Results A total of 153 participants were randomized to an intervention group (77) or a control group (76). After 6 months, the intervention group had a significantly lower systolic blood pressure (135.1 mmHg [±14.8] vs. 142.7 mmHg [±15.0], adjusted mean difference: 8.7 mmHg [95% CI: 3.4, 13.9], p < 0.001) and a significantly lower diastolic blood pressure (83.5 mmHg [±8.8] vs. 87.00 mmHg [±9.0], adjusted mean difference: 5.4 [95% CI: 2.9, 7.8], p < 0.0001). The intervention group also had significantly more patients who achieved successful blood pressure control (<140/90 mmHg; 54.4% vs. 32.9%, p = 0.011). Discussion Self-monitoring of blood pressure in combination with self-management of hypertensive medications, diet, and physical activity in a primary care setting leads to significantly lower blood pressure in patients with poorly controlled hypertension. Clinical Trial Registration:ClinicalTrials.gov, identifier ISRCTN14433778.